The Quality Control and Pharmaceutical Analysis of Nonvolatile and Volatile Bioactive Compounds in Chinese Herbal Medicine by HPLC and GC - Yuan, Xudong; Hu, Minyi; Ling Koh, Hwee; Keung Chui, Wai (Current Pharmaceutical Analysis, 2011)
Herbal medicine is becoming more and more popular and has been widely used in the world. However, the quality control is a major issue for different types of herbal products. In this study, a combination of high performance liquid chromatography (HPLC) and gas chromatography (GC) analytical methods was successfully employed for the pharmaceutical analysis and quality control of herbal medicine. Five different brands of a popular Chinese herbal medicine “Yin Qiao Jie Du” tablets were chosen as the model products for the purpose of analysis and quality control. After optimization and validation, HPLC and GC methods were applied to quantify the contents of nonvolatile bioactive compounds glycyrrhizin, chlorogenic acid, and volatile ingredient menthol, respectively. The results revealed significant content variations of active ingredients among different brands of tablets. Glycyrrhizin ranges from 0 to 2.672 mg in one tablet, chlorogenic acid ranges from 0.416 to 2.453 mg, while menthol ranges from 0 to 0.1666 mg, indicating different quality of the same product from various manufacturers. This study demonstrated that the combination of HPLC and GC methods can be used to quantify both the nonvolatile and volatile active ingredients in herbal medicines and thus control their quality.
Keywords: Chlorogenic acid